Probing the toxicity mechanism of multiwalled carbon nanotubes on bacteria - Hartono, Maria Regina (2019)
Carbon nanotubes (CNTs) have emerged recently as superior adsorbent materials for the removal of recalcitrant pollutants. The potential of combining the sorption capability of CNTs with bacterial degradation for pollutant removal, however, necessitates further investigation of the mechanisms of CNTs’ toxicity towards bacterial cells. In this study, we used a panel of stress-responsive recombinant Escherichia coli bioluminescence bacterial strains to explore the possible mechanisms of toxicity of multiwalled carbon nanotubes (MWCNTs). The effects of MWCNTs on markers of oxidative stress, protein, DNA, and membrane damage enabled the exposition of some of the mechanisms of their antimicrobial properties. Using both a bioluminescence bioreporter panel and live/dead staining, we observed that membrane damage played a role in the toxicity of MWCNTs. A subsequent viability study using three strains of bacteria—two gram-negative (Escherichia coli, Pseudomonas aeruginosa) and one gram-positive (Bacillus subtilis)—showed significant MWCNT toxicity in hypotonic water and phosphate-buffered saline solution, compared with the MWCNT toxicity towards the same bacteria incubated in isotonic-rich media. Using a field-emission scanning electron microscope, we demonstrated that membrane damage is caused largely by MWCNTs trapping bacteria and piercing the cell walls. As a result of our observations, we propose integrating MWCNTs and bacteria degradation for pollutant removal in nutrient-rich media to minimize the toxicity effect of CNTs.